Re-creation of the Chinese National Identity through the Beijing Olympic Games - Sun, Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: This paper represents a component of a research report associated with the national social science research program initiated in 2007, entitled "Cultural consciousness of Beijing Olympic Games". Globalization has weakened the national identity of developing countries and initiated an identity crisis. Through use of the example of the Beijing Olympic Games with respect to national identity the Chinese people`s cultural consciousness will be explored and constructed. Methods Review of the literature and the results of expert interviews form the basic information used in this paper. Results National identity refers to: confirmation of national values, the national attribution and national identification and social functions of the national identity. The latter relates to: (1) cohesion function: that is, connecting the will of the people and promoting national competitiveness; (2) integration function: stabilizing the society so as to upgrade the overall national strength; (3) orientation function: forming common values and inheriting national culture, (4) inspiration function: inspiring the national creativity, (5) differentiating function: distinguishing alter ego from ego. Serious challenges to the national identity at present include: (1) the rise of Western cultural trends, (2) growth in foreign entertainment and culture (3) acceptance by Chinese youth of Western festivals; (4) Popularity of the Internet and (5) Taiwanese decision to join the United Nations. The crisis with respect to the national identity includes: (1) people`s fascination for the western culture, (2) damage to national self-esteem, (3) the native national culture being despised, (4) traditional values not being maintained and (5) lack of confidence in the future of the nation. The Beijing Olympic Games may re-create and strengthen the Chinese national identity as a function of : (1) the successful biding for the Olympic Games which greatly eliminated the sense of national inferiority and , enhancing the national self-confidence and sense of pride, (2) The exhibition of the famous historical cities demonstrating Chinese history, (3) the "Humanistic Olympics" designed to promote the core values of Chinese culture, (4) exhibition of Chinese culture in the Olympic Games draws more people to its charm, (5) the performances of the Chinese athletes will stimulate the national spirit, and (6) successful hosting of the Beijing Olympic Games is hoped to show the capability and wisdom of the Chinese nation. Conclusions The Beijing Olympic Games provides an important opportunity for arousing and re-creating China`s national identity and will have a significant impact on enhancement of the Chinese national identity on the world stage.